At the “Junction” of Spinal Muscular Atrophy Pathogenesis: The Role of Neuromuscular Junction Dysfunction in SMA Disease Progression - B. Goulet, B.; Kothary, R.; J. Parks, R. (Current Molecular Medicine, 2013)
Spinal muscular atrophy (SMA) is caused by mutations that reduce the level of the survival motor neuron protein (SMN) resulting in death of alpha-motor neurons, yet it is unclear why these cells are preferentially affected by a reduction in this ubiquitously-expressed protein. In mouse models of SMA, one of the earliest events detected is defects at the neuromuscular junction (NMJ). Although NMJs are established at a normal frequency, there are structural as well as functional perturbations and a lack of maturation of the primitive synapse. These early defects are followed by loss of the NMJ, denervation of the muscle and onset of muscle atrophy. In this review, we discuss our current understanding of the contribution of NMJ dysfunction in SMA disease pathogenesis, and also provide an overview of therapies currently under preclinical and clinical development for treatment of SMA.
Keywords: spinal muscular atrophy